2004
DOI: 10.1292/jvms.66.555
|View full text |Cite
|
Sign up to set email alerts
|

Complete Nucleotide Sequences of S1 and N Genes of Infectious Bronchitis Virus Isolated in Japan and Taiwan

Abstract: ABSTRACT. The complete nucleotide sequences of the S1 and N genes of three Japanese and one Taiwanese field strains of IBV are reported. These Japanese strains were found to have S1 sequences most similar to those of Australian strains and N sequences most similar to those of North American strains. This result suggested that these Japanese strains might all be recombinant viruses derived from recombination of Australia-and North America-related viruses. Moreover, the S1 proteins of all these Japanese and Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 11 publications
5
24
0
Order By: Relevance
“…However it is necessary to confirm the intergenic recombination event by sequencing larger gene segments, as extensively reported (Estevez et al, 2003;Huang et al, 2004;Shieh et al, 2004;Jackwood et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…However it is necessary to confirm the intergenic recombination event by sequencing larger gene segments, as extensively reported (Estevez et al, 2003;Huang et al, 2004;Shieh et al, 2004;Jackwood et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…So far, based on phylogenetic analysis of the S1 and N genes, genetic recombinants of IBV were suspected to exist in several countries including Japan [1, 8,21,27]. Moreover, based on phylogenetic analysis of several regions of the S2 gene, the Japanese KB8523 strain [22] was considered to be a potential recombinant [12].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Zwaagstra et al [8] reported that the N gene is highly conserved among different IBV isolates. Nevertheless, analysis based on S1 and N gene sequences may provide valuable information on the evolutionary of IBV [9][10][11]. Hence, this study focus on the molecular characterization and phylogenetic analysis of the structural (S1, S2, M, and N) genes of two Malaysian IBV isolates, MH5365/95 and V9/04.…”
Section: Introductionmentioning
confidence: 99%